Use of genomics & proteomics in studying lipase producing microorganisms & its application - Debashrita Majumder; Ankita Dey; Srimanta Ray; Debasmita Bhattacharya; Moupriya Nag; Dibyajit Lahiri (Food Chemistry: Molecular Sciences)
In biotechnological applications, lipases are recognized as the most widely utilized and versatile enzymes, pivotal in biocatalytic processes, predominantly produced by various microbial species. Utilizing omics technology, natural sources can be meticulously screened to find microbial flora which are responsible for oil production. Lipases are versatile biocatalysts. They are used in a variety of bioconversion reactions and are receiving a lot of attention because of the quick development of enzyme technology and its usefulness in industrial operations. This article offers recent insights into microbial lipase sources, including fungi, bacteria, and yeast, alongside traditional and modern methods of purification such as precipitation, immunopurification and chromatographic separation. Additionally, it explores innovative methods like the reversed micellar system, aqueous two-phase system (ATPS), and aqueous two-phase flotation (ATPF). The article deals with the use of microbial lipases in a variety of sectors, including the food, textile, leather, cosmetics, paper, detergent, while also critically analyzing lipase-producing microbes. Moreover, it highlights the role of lipases in biosensors, biodiesel production, tea processing, bioremediation, and racemization. This review provides the concept of the use of omics technique in the mechanism of screening of microbial species those are capable of producing lipase and also find the potential applications.